Peningkatan Keterampilan Gerak Fundamental pada Pelajaran PJOK Melalui Circuit Game bagi Murid Disabilitas Intelektual - Evita Damayanti Hsb; Elsa Efrina; Nurhastuti; Safaruddin Safaruddin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Physical Education (PJOK) learning for students with intellectual disabilities requires structured, varied activities and opportunities for repeated practice because conventional movement learning methods tend to be less able to maintain attention and accommodate their learning needs. This study examines the application of circuit games in improving fundamental movement skills in PJOK learning for students with intellectual disabilities at SLB N Mandailing Natal. The study used the Classroom Action Research (CAR) model of Kemmis and Taggart, which was implemented in two cycles, each consisting of four meetings. Two students with intellectual disabilities were selected purposively based on an initial assessment that showed obstacles in the locomotor, non-locomotor, and manipulative aspects of movement. Data were collected through observation, performance tests, and documentation, then analyzed descriptively quantitatively using percentages with a success indicator of ≥60% per student. The results of the initial assessment showed that student B obtained a score of 43% and student R 50%. After the first cycle, the scores increased to 67% and 80%. In the second cycle, media modifications were carried out by simplifying obstacles, using more attractive and appropriate tools according to students' abilities, and gradually reducing teacher assistance. As a result, student B achieved 97% and student R 100%. These findings indicate that circuit games effectively improve fundamental motor skills through activities that are adaptive, gradual, and appropriate to the learning characteristics of students with intellectual disabilities.